Trimetazidine Decreases Risk of Contrast-Induced Nephropathy in Patients With Chronic Kidney Disease: A Meta-Analysis of Randomized Controlled Trials. (November 2015) - Nadkarni, Girish N.; Konstantinidis, Ioannis; Patel, Achint; Yacoub, Rabi; Kumbala, Damodar; Patel, Rajan A. G.; Annapureddy, Narender; Pakanati, Krishna Chaitanya; Simoes, Priya K.; Javed, Fahad; Benjo, Alexandre M.
Objectives: We sought to synthesize and analyze the available data from randomized controlled trials (RCTs) for trimetazidine (TMZ) in the prevention of contrast-induced nephropathy (CIN). Background: Contrast-induced nephropathy after coronary angiography is associated with poor outcomes. Trimetazidine is an anti-ischemic drug that might reduce incidence of CIN, but current data are inconclusive. Methods: We searched MEDLINE/PubMed, EMBASE, Scopus, Cochrane Library, Web of Science, and ScienceDirect electronic databases for RCTs comparing intravenous hydration with normal saline (NS) and/or N -acetyl cysteine (NAC) versus TMZ plus NS ± NAC for prevention of CIN. We used RevMan 5.2 for statistical analysis with the fixed effects model. Results: Of the 808 studies, 3 RCTs met criteria with 290 patients in the TMZ plus NS ± NAC group and 292 patients in the NS ± NAC group. The mean age of patients was 59.5 years, and baseline serum creatinine ranged from 1.3 to 2 mg/dL. Trimetazidine significantly reduced the incidence of CIN by 11% (risk difference 0.11; 95% confidence interval, 0.16-0.06; P < .01). There was no significant heterogeneity between the studies (I 2 statistic = 0). The number needed to treat to prevent 1 episode of CIN was 9. Conclusions: The addition of TMZ to NS ± NAC significantly decreased the incidence of CIN in patients undergoing coronary angiography. In conclusion, TMZ could be considered as a potential tool for prevention of CIN in patients with renal dysfunction.